Attitudinal Congruence and Similarity as Related to Interpersonal Evaluations in Manager-Subordinate Dyads - Wexley, Kenneth N.; Alexander, Ralph A.; Greenawalt, James P.; Couch, Michael A. (Academy of Management Journal, 1980)
This field study examined the relationship of both actual similarity and perceptual congruence with job satisfaction and performance evaluation in 194 manager-subordinate dyads. Among other findings, congruence between the subordinate's description of the manager and the manager's self-description was significantly correlated with the subordinate's satisfaction. Congruence between the manager's description of the subordinate and subordinate's self-description was significantly related to the manager's evaluation of the subordinate's job performance.